Smithsonian physical tables - Forsythe, William Elmer, 1881- (Smithsonian miscellaneous collections, 2003)
Comprising 901 tables concentrating on a broad scope of common physical and chemical data, the information provided is of general interest to scientists and engineers and of particular interest to those involved with physics in its larger sense. On knovel, the Smithsonian physical tables are now easy to navigate and are full-text searchable as are all references on knovel. All entries in the index are hyperlinked to their page numbers.